الحاجة إلى تفعيل حوكمة هيئات الرقابة الشرعية -بالإشارة إلى حالة السودان- - جوادي, سميرة (جامعة الوادي - University of Eloued, 2019)
تتميز الصناعة المالية الإسلامية بصفة أساسية بوجود عنصر الرقابة الشرعية والتدقيق الشرعي، كما أن الالتزام بمبادئ الشريعة الإسلامية لدى المؤسسات المالية الإسلامية يعد الشرط الأساسي لنجاح ومصداقية ومشروعية معاملاتها وأنشطتها، وتعبر الحوكمة الشرعية عن الإجراءات والمعايير التي تزيد من فعالية الرقابة الشرعية لدى هذه المؤسسات سواء من ناحية الرقابة والياتها أو طريقة إظهارها للأطراف ذات العلاقة، لذا وبالتالي فان الغرض الأساسي في إطار تطبيق حوكمة هيئات الرقابة الشرعية ضمان استمرار التقيد بالشريعة الإسلامية في جميع الأوقات وعلى كل المستويات. The Islamic financial industry is characterized primarily by the presence of Sharia supervision and Shari'a auditing. Compliance with Shari'ah principles in Islamic financial institutions is the prerequisite for the success, credibility and legality of transactions and activities. Shari'a governance reflects procedures and standards that increase the effectiveness of Shari'a supervision in these institutions. And therefore the primary purpose within the framework of the application of the governance of Shari'ah Supervisory Bodies is to ensure that Islamic Shari’ah compliance is maintained at all times and at all levels.
Keywords: الحوكمة، الحوكمة الشرعية، هيئات الرقابة الشرعية